Potential Cosmeceuticals from Marine Constituents - L.V, Vigneshwaran; Shaju, Ann Mary (PT. Antis International Publisher, 2024)
Cosmetic pharmaceuticals, or cosmetic goods with drug-like qualities, are the most recent innovation in the pharmaceutical industry. Klingman coined the term